Improving water resources management in rural river basins under competing demands: a case study from the Walawe River Basin, Sri Lanka - Weragala, Neelanga; Kaluarachchi, Jagath J.; Smakhtin, Vladimir U. (2011)
Irrigated agriculture plays an important role in achieving food security in developing countries. As competition for water increases, water transfers from agriculture to other water use sectors should be approached in a scientific manner. Improvements of water use efficiency in agriculture and the optimal water allocation among competing users are seen as feasible solutions to this problem. In situations where water demand exceeds the supply, a holistic management policy is required. This work analyses a rural river basin, the Walawe River Basin in Sri Lanka, where different users face supply shortages while up to 44% of water is still available for use in the basin. The study analyses how the variability in supply and demands can lead to water shortages in the basin. Several demand management scenarios are analyzed to evaluate the effects of irrigation efficiency increase and hydropower production mode on the overall water supply-demand situation. The results provide valuable information for formulating management practices and policies.